PEMANTAUAN DAN EVALUASI SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK PADA PEMERINTAH KOTA BALIKPAPAN BERDASARKAN PERATURAN MENTERI PAN-RB NOMOR 59 TAHUN 2020 - Grandys Frieska Prassida; Giovany Muhammad Rifky (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
The use of information and communication technology in the government environment, which is currently known as the Electronic-Based Government System (SPBE), is absolutely necessary. In fact, the implementation of SPBE needs to be continuously monitored and evaluated periodically in order to ensure the improvement of public service quality in government agencies. This can be referred to the Regulation of the Minister for Administrative Reform and Bureaucratic Reform (Permen PAN-RB) Number 59 of 2020. The monitoring and evaluation of SPBE carried out in this study aims to measure the maturity level of SPBE implementation in the Balikpapan City Government in 2022 with reference to the guidelines contained in Permen PAN-RB Number 59 of 2020. This research establishes several stages in its implementation starting from literature studies, development of monitoring and evaluation instruments, online data collection, calculation of maturity level of SPBE implementation, to analysis of results and recommendations. The final result of the Balikpapan City Government's SPBE index value for 2022 is 3.11, which is included in the "Good" predicate. Most of the indicators in the SPBE Governance and Service domain have met the criteria in Permen PAN-RB Number 59 of 2020. However, several other indicators, particularly in the SPBE Management domain, still have quite low values, so this raises gaps for improvement that are conveyed in the recommendations section in this study.